DANCE AND ETHNICITY: THE PROCESSES OF INCLUSION IN SCHOOL AND SOCIETY (Fiep Bulletin - online, 2011)
It aims to reflect on the relations of ethnicity those are established in society and spread the teaching of dance, seeing these relations possibilities of inclusion of social subjects. It chooses to think this theme in the social sector in general and in particular at school for understanding that in this space, despite the investment, advances to overcome the discriminatory processes has appeared timidly. For its accomplishment, were used articles, theses and dissertations that deal with inclusion and/or ethnicity in the teaching of dance. Selected articles were found primarily in the Catalog of Periodicals produced by the Research Institute Proteoria installed at the Center for Physical Education of the Federal University of Espírito Santo. Also used were articles published in the database of the CAPES, available on the Internet. The study concluded that from the pluralism that dance and the relationship of ethnicity can be found, as they open their doors to understanding the other (which is in each subject). This transformation will not happen without disruption, and especially without the clarification of the historical conditions and not natural, which affect the existence.
Keywords: Dance; Ethnicity; Social Inclusion